2007 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--1633
|View full text |Cite
|
Sign up to set email alerts
|

The Sound Of Materials: Creating Excitement For Materials Engineering And Science In Engineering Technology Programs

Abstract: Previously, she was Associate Dean for the College of Arts and Sciences and served as Chair of Engineering Technology Department from 1995-2002. Since arriving at Western Washington University in 1988, her primary teaching assignments have been in the Manufacturing Engineering Technology program and in the development of the communication skills of engineering technology students; her research interests have been in the materials science of musical instruments, development of concurrent engineering curricula, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The downforce (Fig. 2), amounting to at least 90 N [8], produced by the tension of strings is propagated as static pressure to the violin body. Focusing on the effect on the acoustic characteristics of string pressure, numerical analysis results have shown that the viol [9], which has a very similar structure to the violin, has resonance characteristics in the body structure that change depending on whether or not there is string pressure.…”
Section: Violin Structurementioning
confidence: 99%
“…The downforce (Fig. 2), amounting to at least 90 N [8], produced by the tension of strings is propagated as static pressure to the violin body. Focusing on the effect on the acoustic characteristics of string pressure, numerical analysis results have shown that the viol [9], which has a very similar structure to the violin, has resonance characteristics in the body structure that change depending on whether or not there is string pressure.…”
Section: Violin Structurementioning
confidence: 99%
“…Kaplan et al describe relationships between ABET criteria and music. 31 Recognizing the fact that music resonates with students (creating music, listening to music, playing musical instruments), educators have used this forum to provide interesting projects in engineering and computer science courses 32,33,34,35 that increase students' enthusiasm for learning. While our laboratory activity involves musical instruments, the artistic component is clearly emphasized.…”
Section: Introductionmentioning
confidence: 99%
“…transforming it from a traditional lecture only course to a course focused on conceptual learning with many active and collaborative experiences. During this development period, several papers that outline the various aspects of these changes and describe the resulting changes in student learning outcomes (with remaining challenges) have been published elsewhere [1][2][3][4][5][6][7][8] . Based upon the conclusions drawn from many research studies in engineering education, most of the elements of a student-centered approach are now present in the course: cooperative learning, case-based teaching, active/inquiry learning, concept learning, problem-based learning, and constructive alignment [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…The student response to the two different context areas differed and those differences are highlighted below. However, this paper focuses mainly on the biomedical device context area results since these activities are able to address a broader range of important student learning outcomes in materials engineering and other papers have already described the stringed instrument design approach 2,5 . A previous conference paper describes these newly developed biomedical based activities in much more technical detail 1 .…”
Section: Introductionmentioning
confidence: 99%